How to let go: pectin and plant cell adhesion - Daher, Firas Bou; Braybrook, Siobhan A. (Frontiers in Plant Science, 2015)
Plant cells do not, in general, migrate. They maintain a fixed position relative to their neighbours, intimately linked through growth and differentiation. The mediator of this connection, the pectin-rich middle lamella, is deposited during cell division and maintained throughout the cell’s life to protect tissue integrity. The maintenance of adhesion requires cell wall modification and is dependent on the actin cytoskeleton. There are developmental processes that require cell separation, such as organ abscission, dehiscence, and ripening. In these instances, the pectin-rich middle lamella must be actively altered to allow cell separation, a process which also requires cell wall modification. In this review, we will focus on the role of pectin and its modification in cell adhesion and separation. Recent insights gained in pectin gel mechanics will be discussed in relation to existing knowledge of pectin chemistry as it relates to cell adhesion. As a whole, we hope to begin defining the physical mechanisms behind a cells’ ability to hang on, and how it lets go.